Noise reduction problems of vibratory machines - MICHALCZYK, J. (Archives of Acoustics, 1993)
Several new methods of reduction of the noise produced by vibratory machines, such as conveyors, vibratory tables and sieves, shakeout grates etc. are proposed. Special attention is devoted to the problems of optimization of vibration parameters in the machines mentioned above, with restrictions imposed by the required production output and quality of the manufacturing process. The methods consisting in modification of the character of vibration of housing elements and application of low-tuned coverings in machines are outlined.